Rancang Bangun Media Tes Berbasis Komputer menggunakan Wondershare Quizcreator untuk Mendukung Pembelajaran Daring - Imam Mualim; Nuari Anisa Sivi; Najla Asyila; Oriza Panduwinata (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2023)
The development of information technology provides opportunities for educators to create more efficient and interactive learning evaluation media. This study aims to design and develop a computer-based test media using Wondershare Quiz Creator as a tool to support online learning. The research method used is Research and Development (R&D) with a waterfall model, which includes the stages of needs analysis, design, development, testing, and implementation. The results show that the developed test media is capable of providing various types of questions, such as multiple choice, short answer, true-false, and matching, and is equipped with features such as automatic feedback, time settings, and exportable test results. User testing indicates that the media is easy to use, responsive, and effective in supporting the learning evaluation process in online learning. In addition, educators can quickly create, manage, and distribute tests through digital platforms without requiring advanced technical skills. Thus, the use of Wondershare Quiz Creator has proven to be an alternative solution for providing practical and interactive computer-based test media that supports improving the quality of online learning. This research is expected to serve as a reference for educators in utilizing technology to enhance the effectiveness of learning evaluation